Robotic magnetic navigation-guided pulmonary vein isolation in an atrial fibrillation patient with dextrocardia situs inversus: techniques and potential advantages - Qingzhi Luo; Yun Xie; Liqun Wu; Qi Jin (BMC Cardiovascular Disorders, 2023)
Abstract Background Dextrocardia with situs inversus (DSI) is a very rare congenital anomaly. Catheter manipulation and ablation of atrial fibrillation (AF) in patients with this anatomical variant is challenging for the operators. This case report presents a safe and effective AF ablation guided by the robotic magnetic navigation (RMN) system in combination with intracardiac echocardiograhy (ICE) in a patient with DSI. Case presentation A 64-year-old male with DSI was referred for catheter ablation of symptomatic, drug-refractory paroxysmal AF. One transseptal access was achieved via the left femoral vein under the guidance of ICE. The three-dimensional reconstruction of the left atrium and the pulmonary veins (PVs) were performed by the magnetic catheter using the CARTO and the RMN system. Then, the electroanatomic map and pre-acquired CT images were merged. Finally, bilateral circumferential ablation lines were delivered around the ipsilateral PV ostia to achieve complete PV isolation (PVI). Conclusions This case demonstrates that AF catheter ablation under the guidance of the RMN system using ICE is feasible and safe in a patient with DSI. Moreover, the combination of these technologies broadly facilitates treatment of patients with complex anatomy, while reducing the risk of complications.